VARIATION OF CONCENTRATION ON VIABILITY PROBIOTICS POWDER COATING EFFERVESCENT TABLETS - Lora Lestari Lubis; Devi Ambarwaty Oktavia; Feliatra ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Efforts to increase shrimp production one through the use of probiotics. To maintain the viability of probiotic bacteria it is necessary need to protect bacteria by coating maltodextrin. Next will be molded into effervescent tablets to more intensive in the protection of probiotic bacteria. This study aimed to test the viability (the number of bacteria and soluble) probiotic that has been modified into effervescent tablets with variation in the concentrations of the coating. The method used is an experimental method in which samples of shrimp pond water will be increased 4 effervescent tablets (Formula I, II, III, IV) with 3 coating concentrations of 20%, 30%, and 40% maltodextrin. Each treatment be repeated two times. To determine the concentration of effervescent tablet coating formula is most effective test TPC (Total Plate Count) and the test of time to dissolve. Based on the test showed that the viability (number of bacteria and soluble time) probiotics in effervescent tablets with a coating of maltodextrin the best and the most effective in maintaining the stability of bacteria is of formula IV with a concentration of 30% by number of bacteria of 6.46 log CFU / mL and soluble within 20 menit. tatistical tests, the coating concentration factor (P) and the effervescent tablet formula (Q) has significant effect (p <0.05).Keywords: probiotics, effervescent tablets, Total Plate Count, viability